Analysis of the Challenges Faced by the Families of Veterans with Post-Traumatic Stress Disorder: A Qualitative Study - GoliGarmkhani, Rahim; Amiri, Hassan; GolMohammadian, Mohsen (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The purpose of the present study is to analyze the challenges faced by the families of veterans suffering from post-traumatic stress disorder (PTSD). Methods: This research was conducted using a qualitative approach and grounded theory methodology. The statistical population consisted of 1,500 individuals, and participants were selected through purposive sampling based on the inclusion criteria. Data collection continued until theoretical saturation was achieved, resulting in the study of 42 families, including spouses and children of veterans with PTSD in Kermanshah province. Additionally, a literature review and semi-structured interviews with 10 experts and social work professionals in the field of family studies were conducted over a 12-month period in 2022. Data were analyzed using Strauss and Corbin’s method. Findings: The results were obtained through three stages of open coding, axial coding, and selective coding. Data analysis yielded 138 subcategories, 15 main categories, and 1 core category. The 15 main categories included: "quality of life issues, financial problems, internal family environment challenges, family functioning issues, psychological problems, parent-child relationship problems, challenges from surrounding individuals and social support networks, marital relationship issues, coping strategy problems, personality trait issues, life cycle challenges, organizational and cultural action problems, family outcome challenges, social outcome challenges, and individual outcome challenges." These were presented as causal, intervening, contextual factors, strategies, and outcomes in the final model. Conclusion: This study, in connection with the research literature, provided a new understanding of the experiences of families of veterans with PTSD by describing their challenges. The findings revealed that these families face significant issues in various aspects of their lives, and reducing these challenges requires greater attention from responsible organizations and mental health centers.